2012
DOI: 10.1111/j.1540-5907.2011.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Foundations of Legislative Speech

Abstract: (MPs) dedicate a significant amount of their time to preparing speeches and participating in legislative debates. Yet, political scientists know surprisingly little about the role of political parties in debate, the institutions that govern access to the floor, and the strategic nature of the messages legislators try to convey. We put forward a comparative institutional theory of legislative debate in which we view speeches as the result of strategic choices made by party leaders and backbenchers. As a consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
222
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(247 citation statements)
references
References 41 publications
7
222
1
6
Order By: Relevance
“…Political scientists have only recently started to examine what factors explain speaker selection in legislative debates (Proksch and Slapin 2012;Proksch and Slapin 2015;. Proksch and Slapin (2015) have shown that the degree to which party leaders exercise control over who speaks and what legislators say depends on the electoral system.…”
Section: Limitations and Extensionsmentioning
confidence: 99%
“…Political scientists have only recently started to examine what factors explain speaker selection in legislative debates (Proksch and Slapin 2012;Proksch and Slapin 2015;. Proksch and Slapin (2015) have shown that the degree to which party leaders exercise control over who speaks and what legislators say depends on the electoral system.…”
Section: Limitations and Extensionsmentioning
confidence: 99%
“…It is therefore important to consider whether the party leadership is likely to allow a MP to speak in a debate when explaining floor time of individual MPs. Proksch and Slapin (2012) argue that in systems where parties play an important role (e.g., in Germany or Sweden), party groups have established rules providing their leaders with means to prevent certain MPs from taking the floor. Thus, we should expect parties to strategically decide who is "allowed" to take the floor, even though MPs have some sort of "freedom of speech," and should in general be allowed to participate in debates.…”
Section: The General Incentives Of Parties and Mps In Legislative Debmentioning
confidence: 99%
“…Last, party leaders may use their ability to steer the agenda, to avoid that proposals that would divide the party come to a vote in the legislature. Hence, when aiming to explain speechmaking and legislative behavior in general, we should keep in mind that we need to consider both the preferences and incentives of individual MPs, as well as the party leadership's incentives and ability to steer the agenda and punish and reward MPs (see also Proksch and Slapin 2012).…”
Section: The General Incentives Of Parties and Mps In Legislative Debmentioning
confidence: 99%
“…Plenary speeches can also be used to identify dissenting MPs in national parliaments. However, this approach may introduce bias because speakers are often selected by party leaders based on their ideological proximity to the leadership (Proksch and Slapin, 2012). Second, research on Westminster democracies demonstrates that dissent pays off electorally while progressive career ambitions give MPs incentives to follow the party line.…”
Section: Explaining Individual Voting Behaviour In Parliament Individmentioning
confidence: 99%